Chronostratigraphy elucidates environmental changes in lacustrine sedimentation rates and metal accumulation - Biamont-Rojas, Ivan Edward [UNESP]; Cardoso-Silva, Sheila; Alves de Lima Ferreira, Paulo; Alfaro-Tapia, René; Figueira, Rubens; Pompêo, Marcelo (Springer Nature, 2023)
All changes taking place in a watershed have repercussions on lacustrine environments, being these, the sink of all activities occurring in the basin. Lake Titicaca, the world’s highest and navigable lake, is not unfamiliar with these phenomena that can alter the sedimentation dynamics and metal accumulation. This study aimed to identify temporal trends of sedimentation rates by employing a geochronological analysis (210Pb, 137Cs) and to propose metal background values in Puno Bay, as well as to identify metal concentrations (As, Ba, Ca, Cr, Cu, K, Mg, Mo, Ni, Pb, Zn) in the projected timeline to propose, for the first time, background values in Puno Bay. Two sediment cores were collected from the outer and inner bays. Sediment rate (SR) was calculated through the excess of 210Pb (210Pbxs) applying the Constant Flux Constant Sedimentation (CFCS) model. Results show that SR in the outer bay was 0.48 ± 0.08 cm a−1 and for the inner bay was 0.64 ± 0.07 cm a−1. Sediment quality guidelines (SQGs) did not indicate toxicity was likely to occur, except for As. However, enrichment factors (EFs) indicated that all metal accumulation is geogenic. Climatic factors had a marked influence on sedimentation rates for the outer bay, and in the case of the inner bay, it was a sum of climatic and human-based factors.
Keywords: CFCS model; High-altitude lake; Lake Titicaca; Puno Bay; Sedimentation rate